Spontaneous ectopic tubal pregnancy after laparoscopic tubal sterilisation by segmental isthmic partial salpingectomy - Drakopoulos, P (BMJ Publishing Group, 2014)
A 33-year-old woman with a history of tubal sterilisation, presented to our gynaecological emergency unit with acute abdominal pain and signs of peritonism. The first day of her last menstruation occurred 4 weeks and 4 days before. Urine pregnancy test was positive and transvaginal ultrasound revealed an empty uterus with a heterogeneous mass below the right ovary. We performed a laparoscopy, which confirmed a previous isthmic partial salpingectomy and the presence of an ectopic pregnancy in the right distal remnant tube. Total salpingectomy of the remnant parts of the tube was performed and the postoperative course was uneventful.